EFEKTIVITAS PROGRAM DIRECT MARKETING TERHADAP TINGKAT KUNJUNGAN WISATAWAN DI KABUPATEN CILACAP - Firmansyach, Yufa Ferdian Nova; Marhendi, Mengku (LPPM STIE Muhammadiah Bandung, 2024)
Cilacap Regency, Indonesia, is endowed with significant tourism potential, yet its tourist visitation rates remain comparatively low compared to other destinations in Indonesia. To enhance tourist arrivals, this study explores the effectiveness of direct marketing programs as a strategy to increase tourist visitation rates in Cilacap Regency. This research employs a quantitative approach with a survey design, collecting data from respondents who have visited Cilacap Regency. Independent variables include various direct marketing strategies such as email campaigns, social media promotions, and other online marketing activities. The main dependent variable is the tourist visitation rate. Regression analysis is utilized to test the hypothesis that direct marketing programs significantly contribute to increasing tourist visitation rates. The findings reveal that direct marketing programs have a significant positive impact on tourist visitation rates in Cilacap Regency (p < 0.001). These findings provide crucial implications for the development of more effective tourism marketing strategies in the region and offer empirical grounds for recommendations to local governments and tourism industry stakeholders in designing more focused and successful marketing programs.